Development and validation of a liquid chromatographic-tandem mass spectrometric method for determination of oseltamivir and its metabolite oseltamivir carboxylate in plasma, saliva and urine. - Lindegårdh, N; Hanpithakpong, W; Wattanagoon, Y; Singhasivanon, P; White, N; Day, N (2007)
A bioanalytical method for the analysis of oseltamivir (OP) and its metabolite oseltamivir carboxylate (OC) in human plasma, saliva and urine using off-line solid-phase extraction and liquid chromatography coupled to positive tandem mass spectroscopy has been developed and validated. OP and OC were analysed on a ZIC-HILIC column (50 mm x 2.1 mm) using a mobile phase gradient containing acetonitrile-ammonium acetate buffer (pH 3.5; 10mM) at a flow rate of 500 microL/min. The method was validated according to published FDA guidelines and showed excellent performance. The lower limit of quantification for OP was determined to be 1, 1 and 5 ng/mL for plasma, saliva and urine, respectively and for OC was 10, 10 and 30 ng/mL for plasma, saliva and urine, respectively. The upper limit of quantification for OP was determined to be 600, 300 and 1500 ng/mL for plasma, saliva and urine, respectively and for OC was 10,000, 10,000 and 30,000 ng/mL for plasma, saliva and urine, respectively. The within-day and between-day precisions expressed as R.S.D., were lower than 5% at all tested concentrations for all matrices and below 12% at the lower limit of quantification. Validation of over-curve samples ensured that it would be possible with dilution if samples went outside the calibration range. Matrix effects were thoroughly evaluated both graphically and quantitatively. No matrix effects were detected for OP or OC in plasma or saliva. Residues from the urine matrix (most likely salts) caused some ion suppression for both OP and its deuterated internal standard but had no effect on OC or its deuterated internal standard. The suppression did not affect the quantification of OP.